Indonesian Realistic Mathematics Education-Based Interactive Digital Worksheets: Enhancing Fractions and Numeracy in Primary Education - Eko Windarti; S. Somakim; Erna Retna Safitri; Mohamed Nor Azhari Azman (Profesi Pendidikan Dasar, 2026)
Primary school pupils’ difficulties in understanding the concept of fractions through conventional textbooks highlight the need for interactive and contextual teaching materials to strengthen numeracy. This study aims to develop and test the validity, practicality, and effectiveness of interactive digital worksheets (E-LKPD) based on Indonesian Realistic Mathematics Education (PMRI) for the topic of fractions. The research employed a research and development method using the ADDIE model, comprising the analysis, design, development, implementation, and evaluation stages. The research instruments consisted of a needs analysis questionnaire, an expert validation sheet, a practicality questionnaire, and a learning outcome test. The research results indicate that the E-LKPD falls into the ‘valid’ category, with content expert ratings of 78%, media expert ratings of 94.2%, and language expert ratings of 95.8%. Usability also falls into the ‘very high’ category, with a percentage of 89.25% in the one-to-one test and 87.25% in the small-group test. The effectiveness of the E-LKPD is demonstrated by an N-Gain value of 0.66, which falls into the moderate category. These findings indicate that the PMRI-based interactive E-LKPD is suitable for use as digital teaching material to strengthen primary school pupils’ understanding of fractions and numeracy skills